Correction: Particle shape optimization by changing from an isotropic to an anisotropic nanostructure: preparation of highly active and stable supported Pt catalysts in microemulsions. Issue 13 (10th March 2016) - Parapat, Riny Y.; Wijaya, Muliany; Schwarze, Michael; Selve, Sören; Willinger, Marc; Schomäcker, Reinhard
Abstract : Correction for 'Particle shape optimization by changing from an isotropic to an anisotropic nanostructure: preparation of highly active and stable supported Pt catalysts in microemulsions' by Riny Y. Parapat et al., Nanoscale, 2013, 5, 796–805.